Legal Aspects of Indecent Acts Against Minors: A Case Study of the Medan District Court - Hidayani, Sri (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2023)
Immoral crime is one type of crime, especially when you see the object of being molested, namely a minor. Children are the source of implementing development in the future. As a future generation, it is necessary for children to do things that are detrimental to the child's personal self, especially if these actions are very disturbing for his future. In immoral crimes, many of the victims are minors, therefore parents must pay attention to the growth and development of a child and know the rights and obligations as parents and provide knowledge to children about the rights and obligations of a child in the family and in society. In committing a crime, the perpetrators of the crime will receive sanctions or punishments. We can find out how the process and trial procedures in cases of immoral crimes are and what are the obstacles in the examination process. In this case the punishment received must be in accordance with the crime committed.